Notes on the amazonia museum - CANDOTTI, Ennio (2007)
This paper briefly presents the context, in which the Museum of Amazonia (MUSA) has been set, the main points of the museum’s conceptual project, and how this proposal intends to contribute in broadening the appreciation of biodiversity, and in constructing a model of education that combines science and traditional knowledge.